A Modified Method for Increasing Radiochemical Purity of I-125 for Radiopharmaceuticals - M Maiyesni; M Mujinah; D. Kurniasih; W Witarti; H Hambali; I. Kambali; S. Febriana (National Research and Innovation Agency, 2023)
Iodine-125 (125I) is one of the radioisotopes widely used in radiopharmaceuticals for diagnosis and therapy of various cancers. Recent reports indicate that there has been shortages in the world supply of this radioiodine isotope. One of the absolute requirements good radiopharmaceuticals must meet is radiochemical purity, which generally has to be above 95 %, with an efficiency of over 90 %. The previous investigation shows that the radiochemical purity is low and does not meet the radiochemical requirement. In this work, we aim at improving the previous method by modifying the Jones reductor-based method. The modified method includes reduction and uniformization of Zn particle sizes, Zn particle compaction, and the performance of reduction process in a closed process flow. The Jones reductor converted impurities into products; in this case, iodate (IO3-) and periodate (IO4-) impurities were converted into iodide (I-), so that 125I product fulfills the radiochemical purity requirements and yielded high efficiency. In this investigation, the 125I previous product was, for the first time, improved with a radiochemical purity of 99.24 % and an efficiency of 97.98 %.